MYTH OF VIOLENCE IN VENOM: LET THERE BE CARNAGE (2021) SEMIOTIC ANALYSIS - Pratiwi, Ayu Dian (Pengkajian Amerika, Universitas Gadjah Mada, 2023)
Popular culture is a product created for many people. The audience’s tastes are essential in production. Besides that, popular culture can also describe a culture that exists in society. One popular product that people like is film. Along with the times, the world of cinema also has more exciting story plots and various characters. One is an American film called Venom: Let There Be Carnage. The film shows signs of the violent formula usually used in American cinema. Therefore, this journal discusses Venom, who is an anti-hero who uses much violence to deliver his existence but has a heroic soul, and also Eddie Brock, an ordinary human who acts as a host who has contradictory traits with Venom even though they live in one body—coupled with conflicts with other villains characters such as Carnage and Cletus Kasady. Researchers present signs of violence using dialogues and movie posters as data references. Also, the characteristics of the heroes used using semiotic analysis supported by John Cawelty’s Myth of Violence theory. With this method, the researcher also describes the culture of violence in American society.